Profil Kepercayaan Diri Remaja serta Faktor-Faktor yang Mempengaruhi - Emria Fitri; Nilma Zola; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
The purpose of this study is to describe the confidence of junior high school Dewi Sartika and know the factors that contribute to adolescent self-confidence. This research uses a quantitative approach in the form of correlation. The populations in this study are students of SMP Dewi Sartika Class VII and VIII, amounting to 256 students. The sample of the study amounted to 156 people determined using the technique of Proportional Random Sampling. The instrument is adapted from a self-confidence instrument with a value of a reliability coefficient of 0.884. Data analysis used descriptive analysis of norm criteria and hypothesis test using double regression with SPSS program. The result of research is most of the confidence of adolescents are in medium category, and optimistic aspect is an aspect which most contribute to teen confidence that is equal to 23, 04%.